In vivo antifungal activity and biocompatibility of Cryptocarya moschata - de Oliveira Zoccolotti, Jacqueline [UNESP]; Cavalheiro, Alberto José [UNESP]; Tasso, Camilla Olga [UNESP]; de Oliveira, Caroline Correa [UNESP]; Ribas, Beatriz Ribeiro [UNESP]; Ferrisse, Túlio Morandin [UNESP]; de Souza Costa, Carlos Alberto [UNESP]; Jorge, Janaina Habib [UNESP] (Springer Nature, 2022)
The objective of this study was evaluate, in vivo model, the antifungal activity of Cryptocarya moschata extract against Candida albicans and its biocompatibility. The animals (N = 50) were divided into groups (n = 5): CI/CG: candidiasis was induced and treated with C. moschata extract (0.045 g/mL); CI/NG: candidiasis was induced and treated with nystatin; CI/NT: candidiasis was induced and no treated; CI/CG-2: candidiasis was induced and treated with C. moschata extract (0.045 g/mL), reapplied after 24 h; CI/NG-2: candidiasis was induced and treated with nystatin, reapplied after 24 h; NCI/NT: candidiasis was not induced and no treated; NCI/CG: candidiasis was not induced and treated with C. moschata extract (0.045 g/mL); NCI/NG: candidiasis was not induced treated with nystatin; NCI/CG-2: candidiasis was not induced and treated with C. moschata extract (0.045 g/mL), reapplied after 24 h; NCI/NG-2: candidiasis was not induced and treated with nystatin, reapplied after 24 h. The fungi present in the lingual dorsum of mice were collected and analyzed by the count of colony-forming units. In addition, histological analysis was performed. Histologically, there was no cell damage in the mice's tongue, and there was a decrease in Candida biofilm, similar to the use of nystatin. It was concluded that the C. moschata extract was effective against C. albicans and was biocompatible.
Keywords: Antifungal; Biocompatibility; Candidiasis; Medicinal plant